Baricitinib improves symptoms in patients with moderate-to-severe atopic dermatitis and inadequate response to topical corticosteroids: patient-reported outcomes from two randomized monotherapy phase III trials. (3rd April 2022) - Reich, K.; DeLozier, A. M.; Nunes, F. P.; Thyssen, J. P.; Eichenfield, L. F.; Wollenberg, A.; Ross Terres, J. A.; Watts, S. D.; Chen, Y.-F.; Simpson, E. L.; Silverberg, J. I.
Abstract: Background: Itch, skin pain, and sleep disturbance are burdensome symptoms in atopic dermatitis (AD) that negatively influence a patient's quality of life (QoL). Objective: To evaluate the impact of baricitinib on patient-reported outcomes (PROs) in adult patients with moderate-to-severe AD, and explore the association between improvement in key signs and symptoms of AD with improvements in QoL and patient's assessment of disease severity. Methods: Data were analyzed from two phase III monotherapy trials (BREEZE-AD1/BREEZE-AD2) in which patients were randomized 2:1:1:1 to once-daily placebo, baricitinib 1-mg, 2-mg, or 4-mg for 16 weeks and assessed using PRO measures. Results: At week 16, baricitinib 4-mg and 2-mg significantly reduced itch severity (Itch Numeric Rating Scale (NRS) (BREEZE-AD1: percent change from baseline −36.6% and −29.4% vs. placebo (–12.0%), p ≤.001 and p ≤.05; BREEZE-AD2: −47.2% and −46.9% vs. placebo (–16.6%), p ≤.001). Baricitinib significantly reduced SCORing AD (SCORAD) pruritus (4-mg in BREEZE-AD1 and 2-mg in BREEZE-AD2) and Patient Oriented Eczema Measure (POEM) itch (both doses). Improvements in skin pain severity and sleep disturbance were also observed. Improvements in AD symptoms showed higher correlations with patients' assessment of AD severity and QoL than improvements in skin inflammation. Conclusions: Baricitinib significantly improved symptoms in patients with moderate-to-severe AD. ClinicalTrials.gov identifiers: NCT03334396 (BREEZE-AD1) and NCT03334422 (BREEZE-AD2).